The Concept Of A Modular Approach In Technological Education And The Methodology Of Teaching The “Skullcap Art” Module (Open Herald: Periodical of Methodical Research, 2026)
This article examines the history of the formation, theoretical foundations, and application areas of the modular approach. The stages of development of the idea of modularity from the Industrial Revolution to the present day are highlighted, and its importance in programming, engineering, and the education system is revealed. The article also analyzes the essence, structure, and basic principles of modular learning. Particular attention is paid to the effectiveness of applying the modular approach in technological education, especially in teaching the art of skullcap making. It is emphasized that this approach contributes to the development of students’ independent activity, practical skills, and creative thinking. As a result, the important role of the modular approach in improving the quality and effectiveness of education is concluded.